The Role of Bhakti Wira Tamtama Hospital Semarang in Covid-19 Prevention and Control - Jarwa Jarwa; Endang Wahyati Yustina; Inge Hartini (Soepra Jurnal Hukum Kesehatan, 2022)
Abstract: Based on Law Number 44 of 2009 concerning Hospitals, it is stated that the Hospital is a health service institution for the community. Hospital is part of the health care system, has a very strategic role in improving the health status of the community. Complete health services are needed during the Covid-19 pandemic. Hospitals are required to provide services in accordance with the standards of the World Health Organization (WHO). WHO in 2020 declared Covid-19 a global pandemic. Indonesia is also affected by the pandemic. The pandemic y has directly caused major changes in Hospital services. This includes the Bhakti Wira Tamtama Hospital in Semarang, which is an Army Hospital under the Military Command.The purpose of this study was to obtain an overview of the regulation and implementation of the roles and factors that influence the prevention and control of Covid-19. The research method used is qualitative research. Primary data was taken from direct interviews with sources, namely the task force Covid, management and patients and their families. The method of analysis using qualitative data analysis.Research result. The Bhakti Wira Tamtama Hospital has a Covid-19 alert status. Handling began at the start of the pandemic. 112 regular beds and 4 ICU beds were prepared from a total of 187 beds for the isolation of Covid-19 patients and 63 of the 332 health workers were prepared for the handling and prevention of Covid-19. The role of the Bhakti Wira Tamtama Hospital in dealing with the Covid-19 outbreak is in accordance with the Outbreak Law, Health Quarantine Law, Health Law, Hospital Law, Presidential Decree No. 11 of 2020, the Governor of Central Java's Decree, namely to participate in overcoming the outbreak starting from from screening, patient care, education to the return of the bodies of Covid-19 patients. The purpose of setting the role is to carry out Health Quarantine in accordance with the Health Quarantine Act. The mechanism for implementing its role is in accordance with and in line with regulations from the Central and Regional Governments. The hospital team consists of the screening, education, laboratory, nursing, disinfection and corpse recovery teams. The form of the role can be in the form of imperative and facultative roles. The influencing factors when viewed from juridical factors are in accordance with existing laws and regulations, social factors by dismissing the notion of "coviding" patients and technical factors with the limited number of health workers and special isolation rooms.Keywords: Health services, role, prevention, Covid-19, Abstrak: Rumah Sakit merupakan bagian sistem pelayanan kesehatan, memiliki peran sangat strategis dalam meningkatkan derajat kesehatan masyarakat. Pelayanan kesehatan yang paripurna dibutuhkan di saat pandemi Covid-19. Rumah Sakit dituntut untuk memberikan pelayanan sesuai dengan standar Badan Kesehatan Dunia (WHO). WHO pada tahun 2020 menetapkan Covid-19 merupakan pandemi dunia. Pandemi secara langsung menyebabkan perubahan besar layanan Rumah Sakit. Termasuk juga Rumah Sakit Bhakti Wira Tamtama Semarang yang merupakan Rumah Sakit Tentara yang berada dibawah Kodam.Hasil penelitian, Rumah sakit Bhakti Wira Tamtama berstatus siaga Covid-19. Penanganan dimulai sejak awal pandemi. Peran Rumah Sakit Bhakti Wira Tamtama untuk penanggulangan wabah Covid-19 sudah sesuai dengan Undang-Undang Wabah, Undang-Undang Kekarantinaan Kesehatan, Undang-Undang Kesehatan, Undang-Undang Rumah Sakit, Keppres Nomor 11 Tahun 2020, Keputusan Gubernur Jateng yaitu ikut serta dalam penanggulangan wabah mulai dari skrining, perawatan penderita, edukasi sampai dengan pemulasaran jenazah pasien Covid-19. Tujuan pengaturan peran untuk menyelenggarakan kekarantinaan Kesehatan sesuai dengan Undang-Undang Kekarantinaan Kesehatan. Mekanisme pelaksanaan perannya, sesuai dan sejalan dengan peraturan-peraturan dari Pemerintah Pusat maupun daerah. Tim rumah sakit terdiri dari tim skrining, edukasi, laboratorium, keperawatan, desinfeksi dan tim pemulasaran jenazah. Bentuk perannya dapat berupa peran imperative dan fakultatif. Faktor-faktor yang mempengaruhi bila ditinjau dari faktor yuridis sudah sesuai dengan peraturan perundangan yang ada, faktor sosial dengan menepis anggapan untuk meng”covid”kan pasien dan faktor teknis dengan terbatasnya jumlah tenaga kesehatan dan ruangan khusus isolasi.Kata kunci: Pelayanan kesehatan, peran, penanggulangan, Covid-19,